HUBUNGAN PENGETAHUAN DAN SIKAP BIDAN TERHADAP PERTOLONGAN PERSALINAN PADA PENDERITA HIV/AIDS DI WILAYAH KABUPATEN BOYOLALI - Nurul Eko Widiyastuti; Sri Madya Bhakti Eka Rini (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Facts found in Boyolali occurred in the number of people living with HIV / AIDS an average of10 new people every month. Also found that people with HIV / AIDS children and motherswere relatively untouched because there has been no massive program. Recorded 211 cases ofHIV / AIDS in Boyolali, until the beginning of November 2013, there were 6 people living withHIV / AIDS who died. There are still some midwives who have the wrong understanding andthere is still refusing to provide aid delivery in pregnant women suspected of HIV / AIDSbecause of the tendency to make a referral to the service designated to handle the case ofdelivery assistance to PLHIV. This study includes Ex-postfacto with causal comparativeresearch, the instrument uses a Likert questionnaire models. The population of all midwives inthe region of Boyolali totaling 483 people, with a purposive sample of random samplingtechnique. Test the validity of the instrument using the product moment correlation coefficient,and reliability test using Cronbach Alpha. Using a computer-assisted data processing with SPSSversion 16.0 for Windows. The results of multiple linear regression analysis showed Y = -4331+ 0037 (X1) + 0.097 (X2). Probability value obtained models are statistically significant 0.000ashows that the proposed alternative hypothesis is accepted, which means that the independentvariable partial effect on aid delivery in patients with HIV / AIDS. Thus, it can be said that thereis a significant relationship of knowledge and attitudes of midwives to help labor in patientswith HIV / AIDS. The better the knowledge, the better the midwife attitudes about HIV / AIDSand this will affect the delivery assistance to people with HIV / AIDS. Keywords: Knowledge, Attitude, HIV / AIDS